Amyloidosis—a Complication of Pustular Psoriasis. Issue 5653 (10th May 1969) - Berger, Peter A.
Abstract : Two patients with generalized pustular psoriasis developed amyloidosis with a fatal outcome. It is suggested that generalized pustular psoriasis may predispose to the development of secondary amyloidosis either by prolonged stimulation of the reticuloendothelial system or through abnormal immunoglobulin synthesis.